2020
DOI: 10.1002/mgg3.1431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and genotype‐phenotype correlations of 130 Chinese children in a high‐homogeneity single‐center cohort with 5α‐reductase 2 deficiency

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…Patients diagnosed with 5α‐RD from March 2009 to February 2020 were included 19 . The diagnosis was made based on the clinical characteristics, the testosterone/DHT ratio, and SRD5A2 variants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients diagnosed with 5α‐RD from March 2009 to February 2020 were included 19 . The diagnosis was made based on the clinical characteristics, the testosterone/DHT ratio, and SRD5A2 variants.…”
Section: Methodsmentioning
confidence: 99%
“…Patients diagnosed with 5α‐RD from March 2009 to February 2020 were included. 19 The diagnosis was made based on the clinical characteristics, the testosterone/DHT ratio, and SRD5A2 variants. They all carried homozygous or compound heterozygous SRD5A2 variants that were classified as pathogenic or likely pathogenic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1974, 5α-RD2 was first described clinically and biochemically in studies of Dominican Republic subjects and in two siblings from Dallas, TX, United States (Imperato-McGinley et al, 1974;Walsh et al, 1974). 5α-RD2 is an autosomal recessive 46,XY DSD caused by genetic variants in the SRD5A2 gene, manifested by variable degrees of undervirilization (Fan et al, 2020). The 5α-RD2 manifests as failed or partial masculinization of external genitalia with normal Wolffian ducts, due to impaired activity of the 5-alpha reductase type 2 enzyme (3-oxo-5-alpha-steroid 4 dehydrogenase, 5α-R2).…”
Section: Introductionmentioning
confidence: 99%
“…To date, approximately 180 variants of SRD5A2 gene have been identified, with missense and nonsense mutations being the most common (Human Gene Mutation Database). The NM_000348.4:c.680G>A mutation (NP_000339.2:p.Arg227Gln) was detected in three Vietnamese patients in a homozygous state [ 5 , 8 ] and was one of the most frequent mutations in Asians [ 9 ]. In 2019, Cheng et al first reported a novel SRD5A2 mutation (NM_000348.4:c.485A>C) (NP_000339.2: p.His162Pro) in adult Chinese twins with 5 α RD2 enzyme deficiency [ 10 ].…”
Section: Introductionmentioning
confidence: 99%